Clinical features of renal damage associated with Epstein-Barr virus infection in children - Yang, Xiaoqing; Lin, Baohua; Shen, Tong (Frontiers in Pediatrics, 2023)
Objective: To understand the renal damage and clinical features of pediatric patients with acute Epstein-Barr virus (EBV) infection Methods: In this retrospective observational study, 548 pediatric patients who were admitted to and treated at the Xiamen Women and Children Health Center between January 2017 and December 2021 and who met the criteria of acute EBV infection were selected as participants. The sociodemographic and clinical data of these patients were collected for statistical analysis. The study population was divided into a renal damage group (41 patients) and a non-renal damage group (507 patients), and the characteristics of the two groups were compared. Results: (1) Of the 548 enrolled patients, 340 and 208 were boys and girls, respectively. Among them, 41 patients showed renal damage (renal damage group), including 26 boys and 15 girls, and the incidence rate of renal damage was 7.48%. (2) The major renal involvements in the 41 pediatric patients with acute EBV infection in the renal damage group manifested as hematuria (56.1%), proteinuria (37.71%), hematuria + proteinuria (12.9%), edema (51.22%), hypertension (17.07%), oliguria (4.88%), and acute renal failure (2.44%). (3) The pediatric patients in the renal damage group had statistically significantly longer fever durations, higher blood EBV-DNA loads, and lower blood CD4+/CD8+ T lymphocyte ratios than those in the non-renal damage group. Conclusions: In pediatric patients, the incidence rate of acute EBV-induced renal damage is not low. The clinical manifestations are mostly hematuria or proteinuria, with an overall good prognosis, but occasionally severe renal damage such as acute renal failure. The possibility of secondary renal damage is high when pediatric patients with acute EBV have prolonged fever, high blood EBV-DNA loads, and decreased blood CD4+/CD8+ ratios.